Productivity Of Honeybees In Oil Palm Integrated System In Niger- Delta Of Nigeria - Emuh, FN; Ofuoku, AU (Journal of Agriculture and Environment, 2013)
For two consecutive years in Abbi, Delta State of Niger-Delta of Nigeria one, two and three beehives were integrated in oil palm plantation to determine optimum productivity of the oil-palm honey bee farming system. The fresh fruit bunch (economic yield) of the oil palm was statistically similar at 0, 1, 2 and 3 bee hive(s) per hectare. The honey yield were statistically similar for each bee hive/kg/ha while the total honey yield/production was significantly higher in the order of three > two > one bee hive/ha. Result obtained in this study indicates that productivity of oil palm plantation + three Beehives/ha which produced more honey is recommended. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 38-40 DOI: http://dx.doi.org/10.3126/aej.v12i0.7561